2012
DOI: 10.1037/a0026643
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism, procrastination, and psychological distress.

Abstract: Using a cross-panel design and data from 2 successive cohorts of college students (N = 357), we examined the stability of maladaptive perfectionism, procrastination, and psychological distress across 3 time points within a college semester. Each construct was substantially stable over time, with procrastination being especially stable. We also tested, but failed to support, a mediational model with Time 2 (mid-semester) procrastination as a hypothesized mechanism through which Time 1 (early-semester) perfectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
2
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 67 publications
8
76
2
15
Order By: Relevance
“…The result showed that the students who were younger, were active procrastinators, whereas students who were older, were passive procrastinators (Cao, 2012). Similarly another research by Rice, Richardson and Clark (2012) tried to test if there was a correlation between procrastination, psychological stress and perfectionism. What they found was that students who were active procrastinators, had lower levels of psychological stress than those who were passive procrastinators or even perfectionists (Rice, Richardson, & Clark, 2012); therefore proving the hypotheses presented by Chu and Choi that active procrastination is positive procrastination (Choi & Chu, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result showed that the students who were younger, were active procrastinators, whereas students who were older, were passive procrastinators (Cao, 2012). Similarly another research by Rice, Richardson and Clark (2012) tried to test if there was a correlation between procrastination, psychological stress and perfectionism. What they found was that students who were active procrastinators, had lower levels of psychological stress than those who were passive procrastinators or even perfectionists (Rice, Richardson, & Clark, 2012); therefore proving the hypotheses presented by Chu and Choi that active procrastination is positive procrastination (Choi & Chu, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This finding is consistent with the results of previous studies. Rice et al (2012) reported negative perfectionism to have significant relationships with procrastination and its dimensions (including concentration, time management, and concerns about performing tasks). Flett et al (1992) discussed that people experience procrastination due to their perfectionism.…”
Section: -Discussion and Conclusionmentioning
confidence: 99%
“…Positive or adaptive perfectionism is characterized by setting high, yet accessible, personal standards, seeking order, organization, and excellence in tasks, and feeling satisfied with one's own performance and motivated to achieve positive rewards. On the other hand, negative or maladaptive perfectionism is characterized by unrealistically high standards, excessive concerns about mistakes and cognitive deficits, perception of high pressure from others to be faultless, perception of a huge discrepancy between personal performance and standards, compulsive doubts about one's actions, and avoidance of consequences of one's actions (Rice, Richardson & Clark, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, procrastination has been found to have a negative effect on academic performance (Kim & Seo, 2015;Owens, 1997;You, 2015), job satisfaction (Mohsin & Ayub, 2014), mental health (Fritzsche, Rapp Young, & Hickson, 2003;Mohsin & Ayub, 2014;Rice, Richardson, & Clark, 2012) and self-efficacy (Klassen, Krawchuk, & Rajani, 2008). Using a longitudinal design, Patrzek, Sattler, van Veen, Grunschel, and Fries (2014) examined responses of between 1359 and 2207 university students collected in two waves and found that academic procrastination affected them in different ways and led to academic misconduct, such as using fraudulent excuses, plagiarism and fabrication or falsification of data.…”
mentioning
confidence: 99%